Audience effects in a group‐living bird: How contact call rate is affected by vegetation and group size and composition. Issue 3 (24th March 2023) - Meaux, Estelle; He, Chao; Zeng, Xiaolei; He, Ruchuan; Jiang, Aiwu; Goodale, Eben
Abstract: Contact calling is a ubiquitous behavior of group‐living animals. Yet in birds, beyond a general connection with group cohesion, its precise function is not well‐understood, nor is it clear what stimulates changes in contact call rate. In an aviary experiment, we asked whether Swinhoe's White‐eyes, Zosterops simplex, would regulate their own production of contact calls to maintain a specific rate at the group level. Specifically, we hypothesized that the sudden cessation of the group‐level call rate could indicate an immediate predation threat, and we predicted that birds in smaller groups would call more to maintain a high call rate. We also investigated the effects of environmental characteristics, such as vegetation density, and social stimuli, such as the presence of certain individuals, on the rate of three different contact call types. To calculate mean individual‐level rates, we measured the group‐level rate and divided it by the number of birds in the aviary. We found that the individual‐level rate of the most common call types increased with a greater group size, the opposite pattern to what would be expected if birds were maintaining a specific group‐level rate. Vegetation density did not affect any call rate. However, individual‐level rates of all call types decreased when birds were in subgroups with individuals of differing dominance status, and the rate of some call types increased when birds were with affiliated individuals. Our results do not support the hypothesis that contact calls are related to habitat structure or immediate predation risk. Rather, they appear to have a social function, used for communication within or between groups depending on the call type. Increases in call rates could recruit affiliated individuals, whereas subordinates could withhold calls so that dominants are unable to locate them, leading to fluctuations in contact calling in different social contexts. Abstract : The influence of group size on the contact call rate depends on the type of call. Contact call rate was not related to vegetation density. Call rates changed with the presence of group members of certain rank or affiliation.